A lithium-free, low-expansion, high-heat-resistant ceramic boiler and a preparation method thereof

Through the lithium-free ceramic material formula and improved preparation process, the problems of poor thermal shock resistance and dependence of raw materials are solved, and the domestic and high-performance characteristics of low-expansion and high-heat-resistant ceramic cookers are achieved.

CN118754631BActive Publication Date: 2025-02-25JIANGXI UNIVERSITY OF FINANCE AND ECONOMICS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410749999.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-12
Publication Date
2025-02-25
Estimated Expiration
2044-06-12

AI Technical Summary

Technical Problem

Traditional ceramic cookers have poor thermal shock resistance due to frequent heat fluctuations, and rely on the raw material restrictions of imported spodumene and lithosparia, making it difficult to achieve domestic production.

Method used

Using lithium-free ceramic material formulas, including fused quartz, water-washed slurry, Ganzhou clay, sodium chloride and zirconium tungstate, low-expansion, high-heat-resistant ceramic boiling through ball milling, stale treatment and segmented firing processes, utensil.

Benefits of technology

It has achieved the performance of cold and hot cycles of 660℃-20℃ for more than 600 times without bursting, and has got rid of the dependence on imported spodumene and lithosparia. The raw materials are completely domestically produced, and the products have good acid and alkali resistance and low lead and cadmium dissolution. characteristic.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118754631B_ABST
    Figure CN118754631B_ABST
Patent Text Reader

Abstract

The present invention provides a lithium-free low-expansion high-heat-resistant ceramic boiler and a preparation method thereof, belonging to the technical field of ceramic preparation. The lithium-free low-expansion high-heat-resistant ceramic boiler provided by the present invention comprises, by weight, 40-60 parts of fused quartz, 15-25 parts of washed black mud, 20-50 parts of Ganzhou clay, 1-2 parts of sodium chloride, and 2-8 parts of zirconium tungstate. The ceramic material provided by the present invention does not contain lithium, gets rid of the supply restriction of raw materials that rely on imported spodumene and petalite, has a lower firing temperature than "lithium-containing" materials, has low production costs, and the obtained product has good thermal shock resistance, and does not burst after more than 600 cold and hot cycles at 660℃-20℃.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic preparation, and in particular to a lithium-free, low-expansion, high-heat-resistant ceramic boiler and a preparation method thereof. Background Art

[0002] Household pottery pots and other cooking utensils have always been popular in the market. They have developed from the traditional single soup-making function to frying, stir-frying, stewing, braising, steaming, boiling and other functions. However, traditional ceramics cannot withstand frequent thermal fluctuations, have poor thermal shock resistance, and are prone to cracking during cooking. Using petalite and spodumene as core raw materials to produce low-expansion, high-heat-resistant pottery pots and other products is the current mainstream solution. At present, getting rid of the raw material restrictions of relying on imported Australian spodumene and Zimbabwean petalite and completely localizing the raw materials is an urgent problem to be solved.

[0003] The ceramic industry is an important industry, and ceramic raw materials are the foundation and key of the ceramic industry. It is very urgent to strengthen the raw material supply chain, and it is necessary to enhance the independent and controllable capabilities of the industrial chain supply chain. Therefore, there is an urgent need for a "key process or technology to replace imported petalite feldspar", the raw materials of which are "lithium-free" or "low-lithium" to replace imported "lithium-containing" raw materials and strengthen the raw material supply chain. Summary of the invention

[0004] Based on the above content, the purpose of the present invention is to provide a lithium-free low-expansion high-heat-resistant ceramic boiler and a preparation method thereof. The ceramic material provided by the present invention does not contain lithium, gets rid of the supply restriction of raw materials that rely on imported spodumene and petalite, and has good low-expansion and high-heat-resistant performance. It has the characteristics of no explosion after more than 600 times of 660℃-20℃ hot and cold cycle exchange.

[0005] In order to achieve the above-mentioned purpose, the present invention provides the following technical solution: a lithium-free, low-expansion, high-heat-resistant ceramic boiler, wherein the raw materials include, by weight: 40-60 parts of fused quartz, 15-25 parts of washed black mud, 20-50 parts of Ganzhou clay, 1-2 parts of sodium chloride, and 2-8 parts of zirconium tungstate.

[0006] Preferably, the raw materials include, by weight: 42-55 parts of fused quartz, 18-23 parts of washed black mud, 20-40 parts of Ganzhou clay, 1-2 parts of sodium chloride, and 2-8 parts of zirconium tungstate.

[0007] Preferably, the raw materials include, by weight: 52 parts of fused quartz, 18 parts of washed black mud, 21 parts of Ganzhou clay, 1 part of sodium chloride, and 8 parts of zirconium tungstate.

[0008] Preferably, the fused quartz contains the following components in percentage by mass: 99.95% SiO 2 、0.001%TFe 2 O 30.049%TiO 2 ; The ignition loss of the fused quartz is 0.001%.

[0009] Preferably, the Ganzhou clay contains the following components in percentage by mass: 57.18% SiO 2 、14.16%Al 2 O 3 4.86%TFe 2 O 3 , 2.16%MgO, 5.12%CaO, 0.58%Na 2 O, 3.54% K 2 O, 0.60% TiO 2 , 0.07%MnO, 0.07%P 2 O 5 ,<0.02%BaO,<0.005%Cr 2 O 3 , <0.02% Ni, 0.002% Cu, 0.007% Sr, 0.01% Zr, 0.02% SO 3 ; The loss on ignition of the Ganzhou clay is 11.6%.

[0010] Preferably, the washed black mud contains the following components in percentage by mass: 52.01% SiO 2 、28.69%Al 2 O 3 、2.73%TFe 2 O 3 ,0.55%MgO, 0.32%CaO, 0.12%Na 2 O, 1.48% K 2 O, 1.07% TiO 2 ; The loss on ignition of the washed black mud is 12.81%.

[0011] The present invention also provides a method for preparing the lithium-free, low-expansion, high-heat-resistant ceramic boiler, which comprises mixing the raw materials, ball milling, aging treatment, preparing a green body, drying the green body, and firing to obtain the lithium-free, low-expansion, high-heat-resistant ceramic boiler.

[0012] Preferably, the ball milling is performed to a size of less than or equal to 200 meshes.

[0013] Preferably, the aging treatment is aging for 5-7 days.

[0014] Preferably, the firing step is carried out in seven stages: stage one: 25-150°C, 120 minutes; stage two 150-350°C, 70 minutes; stage three 350-650°C, 80 minutes; stage four 650°C, constant temperature for 10 minutes; stage five 650-1100°C, 110 minutes; stage six 1100-1250°C, 60 minutes; stage seven 1250°C, constant temperature for 30 minutes, and finally cooled to room temperature with the furnace and taken out; the atmosphere during the firing process is a weak oxidizing atmosphere.

[0015] Beneficial technical effects:

[0016] The present invention selects fused quartz with a small thermal expansion coefficient to synthesize a crystal phase with a small thermal expansion coefficient after sintering, and controls the quantity of each component phase through improving the production process to prepare a heat-resistant ceramic with high thermal stability.

[0017] The present invention utilizes fused quartz as the main raw material, and its process level technology completely replaces petalite and spodumene. The "lithium-free" high-performance heat-resistant ceramic series products developed by the present invention have unique process formulas, get rid of the supply restrictions of raw materials such as imported spodumene and petalite, and the raw materials are completely domestically produced. The products break through the key technical bottleneck of more than 600 times of hot and cold exchanges at 660℃-20℃ without cracking, filling the gap in the domestic lithium-free heat-resistant high-temperature porcelain sintering technology.

[0018] The lithium-free, low-expansion, high-heat-resistant ceramic cooker provided by the present invention has the energy-saving characteristics of stable rapid cooling and heating performance at 660°C-20°C, no cracking during rapid cooling and heating, high heat storage, long heat dissipation time, long warmth retention time, etc. It has a wide range of applications and can be used for cooking with various heat sources such as gas, electric stoves, liquefied gas, microwave ovens, infrared rays, etc.

[0019] The lithium-free, low-expansion, and high-heat-resistant ceramic cooking vessel provided by the invention is acid- and alkali-resistant and has extremely low dissolution of dangerous heavy metals such as lead and cadmium, and is a healthy cooking vessel.

[0020] The lithium-free, low-expansion, and high-heat-resistant ceramic boiler provided by the invention has an average linear expansion coefficient of ≤2.0×10-6 / °C between room temperature and 700°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The present invention is a flow chart of the preparation process of the lithium-free, low-expansion, high-heat-resistant ceramic boiler. DETAILED DESCRIPTION

[0022] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0023] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0024] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0025] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0026] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0027] The present invention provides a lithium-free, low-expansion, high-heat-resistant ceramic boiler. The raw materials include, by weight: 40-60 parts of fused quartz, 15-25 parts of washed black mud, 20-50 parts of Ganzhou clay, 1-2 parts of sodium chloride, zirconium tungstate (ZrW 2 O 6 )2-8 servings.

[0028] The present invention uses fused quartz as the main raw material. By selecting fused quartz with a small thermal expansion coefficient, it is sintered with materials such as washed black mud and Ganzhou clay to synthesize a solid solution and a eutectic with a small thermal expansion coefficient. At the same time, the fused quartz can also improve the heat shock resistance of the porcelain pot, making it less likely to break when the temperature changes sharply (i.e., improving thermal stability), thereby enhancing the overall mechanical strength of the porcelain pot.

[0029] The main components of Ganzhou clay and washed black mud are silicon oxide (SiO 2 ) and aluminum oxide (Al 2 O 3 ), of which: (1) a portion of aluminum oxide (Al 2 O 3) and silicon oxide (SiO 2 ) In the present invention, mullite is generated. Mullite is also a ceramic material with good heat resistance. Mullite and ZrW 2 O 6 The formation of eutectic interactions can enhance the high temperature resistance of ceramics; (2) Alumina (Al 2 O 3 ) itself has a high melting point and good heat resistance, and ZrW 2 O 6 Combining to form a eutectic can further improve the overall heat resistance and mechanical strength. (3) Silicon oxide (SiO 2 ) and ZrW 2 O 6 The combination helps to form a stable structure and improve the stability of ceramics at high temperatures. (4) Alumina (Al 2 O 3 ) penetrates into silicon oxide to form a solid solution, which can increase the density and hardness of the ceramic, thereby increasing the bending strength of the ceramic body, making it stronger and more resistant to bending deformation.

[0030] Ganzhou clay and washed black mud contain oxides such as iron oxide, magnesium oxide, calcium oxide, potassium oxide, sodium oxide and titanium dioxide in addition to the main components of silicon oxide and aluminum oxide. These substances have mineralizing and stabilizing effects, promoting the system formed by the above silicon oxide, aluminum oxide and zirconium tungstate to have low expansion and high thermal stability.

[0031] In addition, Ganzhou clay also has the following functions:

[0032] The main raw material of the present invention, fused quartz, has poor plasticity and is not easy to shape. It is necessary to add a certain amount of Ganzhou clay. The role of Ganzhou clay in ceramic firing includes the above-mentioned roles and also has the following roles:

[0033] (1) Enhanced plasticity: It gives the ceramic blank good plasticity, fills in between other particles, makes the blank structure denser, makes it easier to shape, ensures that the blank has a certain strength and stability, and prevents deformation or cracking during processing and firing. Ceramic products of various shapes can be made. (2) Fluxing effect: During the firing process, some Ganzhou clay components play a fluxing role, reducing the sintering temperature of the ceramic blank and promoting the sintering and densification of the ceramic. It plays a certain role in regulating the properties of the solid solution, which can help stabilize the crystal structure and improve heat resistance.

[0034] The role of NaCl in the present invention:

[0035] (1) As a solvent, the raw materials of the present invention, water-washed black mud and Ganzhou clay, both contain alumina. The sintering temperature of alumina is relatively high, and it is not easy to form a solid solution with other substances. NaCl, as a flux, can reduce the sintering temperature of alumina, promote sintering, form a solid solution at a lower temperature, promote the densification of ceramics, make the ceramic structure more uniform, thereby controlling the microstructure and thermal properties of the material, and improving the stability of the ceramic when the temperature changes.

[0036] (2) As a stabilizer

[0037] NaCl as a stabilizer can enhance the ZrW 2 O 6 With SiO 2 , heat resistance and stability of alumina solid solution.

[0038] The zirconium tungstate (ZrW 2 O 6 )’s role:

[0039] The present invention converts ZrW 2 O 6 Composited with fused quartz, washed black mud and Ganzhou clay, a product with a small thermal expansion coefficient (the average linear thermal expansion coefficient of 0℃-700℃ is less than 2×10 -6 / ℃) is a heat-resistant ceramic with low expansion and high temperature resistance and high thermal stability. In addition, it also has the following functions:

[0040] (1) Improve strength and toughness: It can significantly enhance the mechanical properties of ceramics, making ceramic products stronger and more impact-resistant.

[0041] (2) As a toughening material: It effectively improves the brittleness of ceramics and has a toughening effect.

[0042] (3) Improve thermal stability: It helps to improve the stability of ceramics when the temperature changes.

[0043] In some embodiments, the raw materials include, by weight: 42-55 parts of fused quartz, 18-23 parts of washed black mud, 20-40 parts of Ganzhou clay, 1-2 parts of sodium chloride, and 2-8 parts of zirconium tungstate.

[0044] In some embodiments, the raw materials include, by weight: 52 parts of fused quartz, 18 parts of washed black mud, 21 parts of Ganzhou clay, 1 part of sodium chloride, and 8 parts of zirconium tungstate.

[0045] In some embodiments, the fused silica comprises the following components in percentage by weight: 99.95% SiO 2 、0.001%TFe 2 O 3 0.049%TiO2 ; The ignition loss of the fused quartz is 0.001%.

[0046] In some embodiments, the Ganzhou clay contains the following components by mass percentage: 57.18% SiO 2 、14.16%Al 2 O 3 4.86%TFe 2 O 3 , 2.16% MgO, 5.12% CaO, 0.58% Na 2 O, 3.54% K 2 O, 0.60% TiO 2 , 0.07%MnO, 0.07%P 2 O 5 ,<0.02%BaO,<0.005%Cr 2 O 3 , <0.02% Ni, 0.002% Cu, 0.007% Sr, 0.01% Zr, 0.02% SO 3 The loss on ignition of the Ganzhou clay is 11.6%. The Ganzhou clay inspection report was issued by the Jiangxi Ceramic Testing Center National Ceramic Product Quality Supervision and Inspection Center (Jiangxi), with the report number CW20210662 and the report date July 13, 2021.

[0047] In some embodiments, the washed black mud contains the following components by mass percentage: 52.01% SiO 2 、28.69%Al 2 O 3 、2.73%TFe 2 O 3 , 0.55% MgO, 0.32% CaO, 0.12% Na 2 O, 1.48% K 2 O, 1.07% TiO 2 The loss on ignition of the washed black mud is 12.81%. The washed black mud test report is issued by Foshan Youbo Ceramic Analysis and Testing Co., Ltd., with report number H20220923121 and completion date September 25, 2022.

[0048] The present invention also provides a method for preparing the lithium-free, low-expansion, high-heat-resistant ceramic boiler, which comprises mixing the raw materials, ball milling, aging treatment, preparing a green body, drying the green body, and firing to obtain the lithium-free, low-expansion, high-heat-resistant ceramic boiler. See the preparation process flow chart Figure 1 .

[0049] The present invention prepares heat-resistant ceramics with high thermal stability by improving the production process and controlling the amount of each component phase. The prepared ceramic product breaks through the key technical bottleneck of 660℃-20℃ hot and cold exchange for more than 600 times without cracking, filling the gap in the domestic lithium-free heat-resistant high-temperature porcelain sintering technology.

[0050] In some embodiments, the ball milling is performed to a mesh size of less than or equal to 200. The present invention has no special requirements for the ball milling method, and a technical solution well known to those skilled in the art can be selected.

[0051] The particle size of ball milling will have a significant impact on the crystal phase and properties of the resulting ceramic material, mainly including the following aspects:

[0052] 1. Influence on crystal phase: Finer particle size is conducive to the formation of finer grains, which can change the distribution and growth morphology of the crystal phase;

[0053] 2. Impact on performance: Fine particle size usually improves the strength, hardness and other mechanical properties of ceramic materials because fine particles can reduce defects and stress concentration.

[0054] 3. Sintering performance: Fine particle size helps to reduce sintering temperature, increase sintering density, and improve the density and integrity of ceramics.

[0055] In order to obtain ceramic materials with better performance, the present invention preferably uses the above-mentioned ball milling particle size range.

[0056] In some embodiments, the aging process is aging for 5-7 days.

[0057] In some embodiments, the green body is prepared by slurry casting or rolling.

[0058] In some embodiments, the firing step is carried out in seven stages: stage one: 25-150°C, 120 minutes; stage two 150-350°C, 70 minutes; stage three 350-650°C, 80 minutes; stage four 650°C, constant temperature for 10 minutes; stage five 650-1100°C, 110 minutes; stage six 1100-1250°C, 60 minutes; stage seven 1250°C, constant temperature for 30 minutes, and finally cooled to room temperature with the furnace and taken out; the atmosphere during the firing process is a weak oxidizing atmosphere.

[0059] The ceramic sintering process in the present invention is step-by-step sintering. Different chemical reactions occur in different temperature ranges, which will affect the formation of the crystal phase. The crystal phase changes mainly in stage three. Therefore, the heating rate in stage three is controlled to be slower to obtain a suitable crystal phase.

[0060] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0061] The clay used in the embodiment is Ganzhou clay, and its performance parameters are as follows: it contains the following components by mass percentage: 57.18% SiO 2 、14.16%Al 2 O 3 4.86%TFe 2 O 3 , 2.16%MgO, 5.12%CaO, 0.58%Na 2 O, 3.54% K 2 O, 0.60% TiO 2 , 0.07%MnO, 0.07%P 2 O 5 ,<0.02%BaO,<0.005%Cr 2 O 3 , <0.02% Ni, 0.002% Cu, 0.007% Sr, 0.01% Zr, 0.02% SO 3 ; The loss on ignition of the Ganzhou clay is 11.6%.

[0062] The washed black mud contains the following components in percentage by weight: 52.01% SiO 2 、28.69%Al 2 O 3 、2.73%TFe 2 O 3 ,0.55%MgO, 0.32%CaO, 0.12%Na 2 O, 1.48% K 2 O, 1.07% TiO 2 The loss on ignition of the washed black mud is 12.81%.

[0063] The fused silica contains the following components by mass percentage: 99.95% SiO 2 、0.001%TFe 2 O 3 0.049%TiO 2 ; The ignition loss of the fused quartz is 0.001%.

[0064] Example 1

[0065] The preparation method of the lithium-free low expansion high heat-resistant ceramic boiler in this embodiment is as follows:

[0066] Step 1: Ingredients of Blank Materials

[0067] The ceramic boiler blank material is 48 parts of fused quartz, 20 parts of washed black mud, 25 parts of Ganzhou clay, 1 part of sodium chloride, zirconium tungstate (ZrW 2 O 6 ) in a ratio of 6 parts to obtain the mud material of the green body.

[0068] Step 2: Molding

[0069] The green body material is ball-milled to 200 meshes, aged for 7 days, and then formed by slip casting to obtain a green body of a ceramic boiler, which is then dried;

[0070] Step 3. Firing

[0071] The dried green body is placed in an electric kiln for firing. The firing atmosphere is weakly oxidizing and the temperature regime is as follows: the firing regime is specifically divided into seven stages: 25-150°C, 120 min; 150-350°C, 70 min; 350-650°C, 80 min; 650°C, constant temperature for 10 min; 650-1100°C, 110 min; 1100-1250°C, 60 min; 1250°C, constant temperature for 30 min, then cooled to room temperature and taken out from the furnace.

[0072] Example 2

[0073] The preparation method of the lithium-free low-expansion high-heat-resistant ceramic boiler in this embodiment is the same as that in Example 1, except that the ceramic boiler blank material is 50 parts of fused quartz, 19 parts of washed black mud, 25 parts of Ganzhou clay, 1 part of sodium chloride, and 1 part of zirconium tungstate (ZrW 2 O 6 ) and 5 parts of ingredients are mixed in a ratio to obtain the mud material of the green body.

[0074] Example 3

[0075] The preparation method of the lithium-free low-expansion high-heat-resistant ceramic boiler in this embodiment is the same as that in Example 1, except that the ceramic boiler blank material is 52 parts of fused quartz, 18 parts of washed black mud, 21 parts of Ganzhou clay, 1 part of sodium chloride, and 1 part of zirconium tungstate (ZrW 2 O 6 ) in a ratio of 8 parts to obtain the mud material of the green body.

[0076] Example 4

[0077] The preparation method of the lithium-free low-expansion high-heat-resistant ceramic boiler in this embodiment is the same as that in Example 1, except that the ceramic boiler blank material is 45 parts of fused quartz, 21 parts of washed black mud, 29 parts of Ganzhou clay, 1 part of sodium chloride, and 1 part of zirconium tungstate (ZrW 2 O 6 ) are mixed in a ratio of 4 parts to obtain the mud material of the green body.

[0078] Example 5

[0079] The preparation method of the lithium-free low-expansion high-heat-resistant ceramic boiler in this embodiment is the same as that in Example 1, except that the ceramic boiler blank material is 42 parts of fused quartz, 23 parts of washed black mud, 31 parts of Ganzhou clay, 1 part of sodium chloride, and 1 part of zirconium tungstate (ZrW 2 O 6 ) are mixed in a ratio of 3 parts to obtain the mud material of the green body.

[0080] The formula of the lithium-free low expansion and high heat-resistant ceramic boiler in Examples 1-5 is shown in Table 1.

[0081] Table 1 Recipe of lithium-free low expansion high heat-resistant ceramic boiler in Examples 1-5 (parts by mass)

[0082]

[0083] The lithium-free, low-expansion, high-heat-resistant ceramic boilers in Examples 1-5 were tested and the test data are shown in Table 2.

[0084] Performance testing:

[0085] The water absorption rate was tested according to the method specified in the National Standard of the People's Republic of China "Determination Method of Water Absorption of Daily-use Ceramics" GB / T 3299-2011.

[0086] The dissolution of lead and cadmium was tested in accordance with the method specified in the National Standard of the People's Republic of China "National Food Safety Standard Ceramic Products" (GB4806.4-2016).

[0087] The thermal expansion coefficient is tested according to QB / T 1321-2012 "Method for Determination of Average Linear Thermal Expansion Coefficient of Ceramic Materials", and the test temperature range is room temperature to 700°C.

[0088] The thermal stability performance is tested according to the method specified in the light industry standard of the People's Republic of China "Fine Ceramic Cookers" (QB / T2580-2018).

[0089] Table 2 Test data of lithium-free low expansion high heat-resistant ceramic boilers in Examples 1-5

[0090]

[0091] It can be seen from Table 2 that the lithium-free, low-expansion, high-heat-resistant ceramic boiler provided by the present invention is:

[0092] (1) No lead or cadmium leaching was detected.

[0093] (2) Average thermal expansion coefficient from room temperature to 700℃ <2.0×10 -6 / ℃,

[0094] (3) The product has excellent thermal stability and can be subjected to more than 600 or even 620 hot and cold cycles from 660°C to 20°C without bursting.

[0095] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a lithium-free, low-expansion, high-heat-resistant ceramic boiler, characterized in that: By weight, 40-60 parts of fused quartz, 15-25 parts of washed black mud, 20-50 parts of Ganzhou clay, 1-2 parts of sodium chloride and 2-8 parts of zirconium tungstate are mixed, then ball milled and aged to prepare a green body, and the green body is dried and fired to obtain the lithium-free, low-expansion and high-heat-resistant ceramic boiler; The firing steps are divided into seven stages: stage one: 25-150°C, 120 minutes; stage two: 150-350°C, 70 minutes; stage three: 350-650°C, 80 minutes; stage four: 650°C, constant temperature for 10 minutes; stage five: 650-1100°C, 110 minutes; stage six: 1100-1250°C, 60 minutes; stage seven: 1250°C, constant temperature for 30 minutes, and finally cooled to room temperature with the furnace and taken out; the atmosphere during the firing process is a weak oxidizing atmosphere; The Ganzhou clay contains the following components in percentage by mass: 57.18% SiO2, 14.16% Al2O3, 4.86% TFe2O3, 2.16% MgO, 5.12% CaO, 0.58% Na2O, 3.54% K2O, 0.60% TiO2, 0.07% MnO, 0.07% P2O5, <0.02% BaO, <0.005% Cr2O3, <0.02% Ni, 0.002% Cu, 0.007% Sr, 0.01% Zr, 0.02% SO3; the loss on ignition of the Ganzhou clay is 11.6%; The washed black mud contains the following components in percentage by mass: 52.01% SiO2, 28.69% Al2O3, 2.73% TFe2O3, 0.55% MgO, 0.32% CaO, 0.12% Na2O, 1.48% K2O, and 1.07% TiO2; the loss on ignition of the washed black mud is 12.81%.

2. The method for preparing a lithium-free, low-expansion, high-heat-resistant ceramic boiler according to claim 1, characterized in that: Calculated by weight, the raw materials include: 42-55 parts of fused quartz, 18-23 parts of washed black mud, 20-40 parts of Ganzhou clay, 1-2 parts of sodium chloride, and 2-8 parts of zirconium tungstate.

3. The method for preparing a lithium-free, low-expansion, high-heat-resistant ceramic boiler according to claim 1, characterized in that: Calculated by weight, the raw materials include: 52 parts of fused quartz, 18 parts of washed black mud, 21 parts of Ganzhou clay, 1 part of sodium chloride, and 8 parts of zirconium tungstate.

4. The method for preparing a lithium-free, low-expansion, high-heat-resistant ceramic boiler according to claim 1, characterized in that: The ball milling is performed to a size of less than or equal to 200 meshes.

5. The method for preparing a lithium-free, low-expansion, high-heat-resistant ceramic boiler according to claim 1, characterized in that: The aging treatment is aging for 5-7 days.

Citation Information

Patent Citations

  • Lithium-free heat-resistant ceramic and preparation method thereof

    CN117209247A